Development of Islamic Religious Education with a Multicultural Perspective at Aisyiyah Politechnic Pontianak - Muhammad Kholid Ramadhanzi (Journal of Research in Islamic Education, 2025)
Multicultural-based Islamic Religious Education (PAI) is an essential need in Indonesia's diverse society. This study aims to analyze the strategies, implementation, and impact of applying a multicultural approach in PAI learning at Politeknik Aisyiyah Pontianak. The research employed a qualitative descriptive method, collecting data through interviews, observations, and documentation. The findings reveal that the development of multicultural-based PAI integrates values of tolerance, justice, and respect for diversity into the curriculum. The learning process employs interactive methods, such as group discussions and case studies, to enhance student participation. Challenges include students' initial lack of understanding of multicultural values and lecturers' limitations in providing contextual materials.  However, the application of multicultural education has shown positive impacts, including increased student tolerance, reduced prejudice, and the creation of an inclusive learning environment. This study recommends strengthening lecturers’ capacities through training, developing institutional policies that support multicultural education, and conducting further research to evaluate the program's sustainability.  By effectively integrating multicultural values into PAI learning, educational institutions can contribute to fostering a tolerant generation and social harmony within the community.